2020
DOI: 10.1146/annurev-chembioeng-112019-084830
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Organic Frameworks in Separation

Abstract: In the wake of sustainable development, materials research is going through a green revolution that is putting energy-efficient and environmentally friendly materials and methods in the limelight. In this quest for greener alternatives, covalent organic frameworks (COFs) have emerged as a new generation of designable crystalline porous polymers for a wide array of clean-energy and environmental applications. In this contribution, we categorically review the merits and shortcomings of COF bulk powders, nanoshee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 167 publications
0
31
0
Order By: Relevance
“…Two-dimensional covalent organic frameworks (2D COFs) are permanently porous, crystalline, macromolecular sheets that are promising for use in catalysis, , chemical sensing, molecular separations, energy storage, ionic conduction, organic electronics, , or biomedical devices. To realize 2D COFs optimized for these applications, general chemical strategies are needed to produce large-area macromolecular sheets. Groundbreaking investigations have shown that the 2D COF crystalline domain size is greatly affected by factors such as the polymerization chemistry, interlayer interactions, monomer size, presence of hydrogen bonds, and reaction conditions. , However, there is currently no unified understanding of the roles of these factors, nor are there quantitative models that can be used to guide 2D COF synthesis.…”
mentioning
confidence: 99%
“…Two-dimensional covalent organic frameworks (2D COFs) are permanently porous, crystalline, macromolecular sheets that are promising for use in catalysis, , chemical sensing, molecular separations, energy storage, ionic conduction, organic electronics, , or biomedical devices. To realize 2D COFs optimized for these applications, general chemical strategies are needed to produce large-area macromolecular sheets. Groundbreaking investigations have shown that the 2D COF crystalline domain size is greatly affected by factors such as the polymerization chemistry, interlayer interactions, monomer size, presence of hydrogen bonds, and reaction conditions. , However, there is currently no unified understanding of the roles of these factors, nor are there quantitative models that can be used to guide 2D COF synthesis.…”
mentioning
confidence: 99%
“…3 Recently, COFs have attracted researchers' interest because of their intriguing properties such as tuneable composition and high thermal and chemical stability (Fig. 1) 12,13 and have been widely used in a variety of applications including energy conversion 14,15 and storage, 16,17 gas storage, 18,19 catalysis, [20][21][22][23][24][25] optoelectronics, 26,27 sensing, 28,29 drug delivery [30][31][32] and adsorption [33][34][35] to name a few.…”
Section: Introductionmentioning
confidence: 99%
“…43,44 Due to the diversity of organic syntheses, COFs provide promising prospects for materials design, enabling function-and applicationoriented material syntheses. Until now, COFs have been widely used for separation and analysis, [45][46][47][48][49] heterogeneous catalysis, [50][51][52] sensing, 53 optoelectronics, 54 energy and environmental science, [55][56][57][58][59] and biomedicine. 60,61 In recent years, COFs, particularly nanoscale COFs (NCOFs), have joined a huge candidate library of biomedical nanomaterials because of their following unique features.…”
Section: Introductionmentioning
confidence: 99%